ANNUAL PLAN AND CONTROL OF EARNINGS AS INTEGRATION STRATEGY OF THE PERUVIAN INDUSTRIAL PYMES - Arrarte Mera, Raúl Alberto (2010)
The present research aims to demonstrate the need for mandatory use of the technical basis and implementation of a uniform system of Planning and Control Master Profit or short-term budget for all Small and Medium Enterprises (SMEs) based in the industrial PERU, prior to the use of Strategic Business Plan projected the long term. In our country, according to studies by the Ministry of Labour and Social, 95% is represented by Small and Medium Enterprises (SMEs) and only 5% personifies the large corporations. Also, publications of the Superintendency of Tax Administration (SUNAT) state that 60% of domestic enterprises are informal. In the global market the domestic firm, has to deal with large organizations, a very intense competitive situation and hostile, that they enjoy using the Planning and Utility Control on a daily basis, but the average entrepreneur unknown. Noteworthy among the benefits to the micro level, encouraging healthy competition and improving business efficiency at the national and international levels, producing also the employer strengthening the regional integration processes such as the Andean Community of Nations (CAN). The targets we have set to develop this work are: 1. Allow greater understanding of the importance, to know in advance, costs of production or operation and performance of each company in the industrial sector mainly exporter. 2. Relieve the hierarchy that these techniques have for the exercise of healthy competition. Urging the administration to plan more economical use of labor, materials and capital. 3. Develop a foresight culture in human resources business environment, instilling in all levels of government, the habit of proper consideration, careful and appropriate use of all relevant factors before making major decisions. With a specific goal: To propose a model Annual Plan and Utility Control for Short- Term Industrial Peruvian SMEs. With what could be achieved to recommend the establishment of specific curricula in our School of Accounting to prepare specialists in Planning and Control Systems of Utilities both for SMEs and for the different branches of economic activity thus helping to reduce informality business operations, improve decision making, optimize the use of scarce resources of SMEs, supporting the goals of our University and to the economic and social development.